Impact of Israelli-Boycotts on Stock Volatility: A GARCH Analysis of Unilever and Indofood - Hasyim, Fuad; Sukardi, Budi (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
This study examines the impact of boycotts on stock volatility, focusing on three major companies: Unilever Indonesia (UNVR), Unilever Global (ULVR), and PT Indofood Sukses Makmur (INDF). Utilizing the GARCH (1,1) model, the research analyzes the volatility patterns of these stocks over a specified period, incorporating external events such as boycotts. The findings reveal that UNVR exhibits higher volatility compared to ULVR and INDF, indicating its greater sensitivity to market changes. Interestingly, the study finds that the dummy variable representing war events is not significant in explaining stock return volatility, suggesting that such events do not meaningfully impact volatility during the observation period. However, a noticeable decline in stock prices for UNVR and ULVR during the boycott period highlights the nuanced effect of external pressures on market performance. These results underscore the importance of understanding the differential impacts of external events on stock volatility and prices, providing valuable insights for investors and policymakers in managing risk and making informed decisions.